Adult Body Height Is a Good Predictor of Different Dimensions of Cognitive Function in Aged Individuals: A Cross-Sectional Study - Pereira, Vitor H.; Costa, Patrício S.; Santos, Nadine C.; Cunha, Pedro G.; Correia-Neves, Margarida; Palha, Joana A.; Sousa, Nuno (Frontiers in Aging Neuroscience, 2016)
Background: Adult height, weight and adiposity measures have been suggested by some studies to be predictors of depression, cognitive impairment and dementia. However, the presence of confounding factors and the lack of a thorough neuropsychological evaluation in many of these studies have precluded a definitive conclusion about the influence of anthropometric measures in cognition and depression. In this study we aim to assess the value of adult height and weight to predict cognitive impairment and depressive symptoms in aged individuals. Methods and Findings: Cross-sectional study performed between 2010 and 2012 in the Portuguese general community. A total of 1050 participants were included in the study and randomly selected from local area health authority registries. The cohort was representative of the general Portuguese population with respect to age (above 50 years of age) and gender. Cognitive function was assessed using a battery of tests grouped in two dimensions: general executive function and memory. Two-step hierarchical multiple linear regression models were conducted to determine the predictive value of anthropometric measures in cognitive performance and mood before and after correction for possible confounding factors (gender, age, school years, physical activity, alcohol consumption and smoking habits). We found single associations of weight, height, body mass index, abdominal perimeter and age with executive function, memory and depressive symptoms. However, when included in a predictive model adjusted for gender, age, school years and lifestyle factors only height prevailed as a significant predictor of general executive function (β=0,139; p<0,001) and memory (β=0,099; p<0,05). No relation was found between mood and any of the anthropometric measures studied. Conclusions and Relevance: Height is an independent predictor of cognitive function in late-life and its effects on the general and executive function and memory are independent of age, weight, education level, gender and lifestyle factors. Altogether, our data suggest that modulators of adult height during childhood may irreversibly contribute to cognitive function in adult life and that height should be used as part of models to predict cognitive performance.